2013
DOI: 10.1002/alr.21140
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the taste receptor T2R38 correlates with chronic rhinosinusitis necessitating surgical intervention

Abstract: This pilot study investigating the genetics of the bitter taste receptor T2R38 in the context of primary sinonasal surgery demonstrates supertaster patients are less likely to need surgical intervention for chronic rhinosinusitis. Additional study is necessary to ascertain postsurgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 14 publications
5
119
0
1
Order By: Relevance
“…23 The gene encoding T2R38, TAS2R38, has two common polymorphisms in white populations, one that encodes a functional form of the receptor and the other encodes a nonfunctional form. 78 The in vitro studies that identified T2R38 as the host protein receptor for acyl-homoserine lactone quorum sensing molecules were complemented by subsequent in vivo studies that correlated the nonfunctional form of T2R38 with susceptibility to CRS [78][79][80][81][82] and gram-negative upper airway infection. 23 T2Rs are also expressed in solitary chemosensory cells, another cell type of the sinonasal epithelium.…”
Section: Regulation Of Antimicrobial Compoundsmentioning
confidence: 99%
“…23 The gene encoding T2R38, TAS2R38, has two common polymorphisms in white populations, one that encodes a functional form of the receptor and the other encodes a nonfunctional form. 78 The in vitro studies that identified T2R38 as the host protein receptor for acyl-homoserine lactone quorum sensing molecules were complemented by subsequent in vivo studies that correlated the nonfunctional form of T2R38 with susceptibility to CRS [78][79][80][81][82] and gram-negative upper airway infection. 23 T2Rs are also expressed in solitary chemosensory cells, another cell type of the sinonasal epithelium.…”
Section: Regulation Of Antimicrobial Compoundsmentioning
confidence: 99%
“…Further studies [60 ▪ ,61 ▪▪ ,62 ▪▪ ] have demonstrated that TAS2R38 may be a genetic marker for CRS. A retrospective study [60 ▪ ] was carried out using TAS2R38 -genotyped patient samples ( N =28) from individuals who had undergone primary functional endoscopic sinus surgery (FESS).…”
Section: The Role Of Tas2r38 Polymorphisms In Chronic Rhinosinusitismentioning
confidence: 99%
“…2,3 The clinical importance of T2R38 as a biomarker for CRS has been further elucidated by studying polymorphisms in T2R38 that produce decreased receptor functionality and lead to an increased susceptibility to gram-negative infection and recalcitrant CRS. 4,5 Furthermore, the genotype of T2R38 can predict surgical outcomes of patients with nonpolyposis CRS and even biofilm formation. 6,7 T2R38 is known to be expressed in the ciliated epithelial cells of the upper airway.…”
mentioning
confidence: 99%